2019
DOI: 10.1007/s00268-019-05307-1
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Clearance in Trauma Patients with an Unreliable Physical Examination

Abstract: Background The objective of this study was to describe and compare the timing of cervical spine clearance in trauma patients with an unreliable physical examination. Methods We prospectively included adult trauma patients admitted with a cervical collar and an unreliable clinical examination (as defined by the NEXUS criteria) at two level 1 trauma centers: one in the USA (US) and one in Denmark (DK). We excluded patients with cervical spine injuries requiring a collar or surgery as treatment and patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…9 Computed tomography (CT) scan of the cervical spine is therefore considered the most appropriate investigation to exclude cervical spine injury after blunt trauma in obtunded patients. 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Computed tomography (CT) scan of the cervical spine is therefore considered the most appropriate investigation to exclude cervical spine injury after blunt trauma in obtunded patients. 10…”
Section: Introductionmentioning
confidence: 99%
“…9 Computed tomography (CT) scan of the cervical spine is therefore considered the most appropriate investigation to exclude cervical spine injury after blunt trauma in obtunded patients. 10 Although CT scan readily demonstrates fractures and malalignment, it provides limited direct evaluation of ligamentous and soft tissue injury, leading some to advocate the use of magnetic resonance imaging (MRI) to clear the spine and remove cervical collars in unconscious or sedated patients. 11 Schoenfeld and colleagues cautioned in 2010 against reliance on CT imaging alone to "clear the cervical spine" after blunt trauma, due to concerns over significant missed injuries.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In addition, the physical examination for this situation is not necessarily reliable. [6,7] The risk of CSI is higher in patients who cannot be evaluated than that in those who are sober. [2] A large number of studies have demonstrated that cervical computed tomography (CT) is one of the most effective approaches to the clearance of CSI, especially after the appearance of spiral CT. [8][9][10][11] However, the limitation of standard cervical CT (SD-CT, provided by the vendor) occurs when it is applied to uncooperative patients with acute cervical spine trauma.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] In addition, the physical examination for this situation is not necessarily reliable. [ 6 , 7 ] The risk of CSI is higher in patients who cannot be evaluated than that in those who are sober. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…Cervical spine X-Rays are no longer used due to their poor quality (often the whole C-spine is not imaged) and sensitivity; the rate of missed injuries using X-rays may be as high as 20 percent (9). Computed tomography (CT) scan of the cervical spine is thus considered the most appropriate investigation to exclude cervical spine injury after blunt trauma in neurologically-free obtunded patients (10).…”
Section: Introductionmentioning
confidence: 99%